(untitled) (PANGEEA, 2025)
Geopolitics is a relatively new science, developed mainly after World War II. The subject is the type of relations between states. Relationships are: political, economic, commercial, cultural, tourism etc. The paper is an overview of the main contributions to the crystallization and evolution of Romanian Geopolitics, from Ioan Conea, the indisputable theorist of Romanian Geopolitics, until the present experts. It examines the development of geopolitical ideologies and concepts in Romanian school.